Physical Fitness Profile of SDN 3 Batulicin Football Team - Jusran Jusran; Sitti Maifa; Faisal Batennie; Hasnia Hasnia; Arham Syahban; Suhria Suhria (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to determine the physical fitness level of the SDN 3 Batulicin football team. The background of this study is based on the importance of physical fitness as a fundamental foundation for supporting football performance, particularly at the elementary school level. In football, players are required to possess adequate physical capacity in order to maintain playing intensity, execute techniques effectively, and complete matches without experiencing excessive fatigue. Based on preliminary observations, the SDN 3 Batulicin football team showed indications that the players’ fitness condition was not yet optimal; therefore, a systematic assessment was necessary. This study employed a descriptive quantitative approach using a survey method. The research subjects consisted of 25 students, all of whom were members of the SDN 3 Batulicin football team. The instrument used was the Indonesian Physical Fitness Test (Tes Kebugaran Jasmani Indonesia/TKJI) for children aged 10–12 years, which includes the 40-meter sprint, pull-up, sit-up, vertical jump, and 600-meter run. The data were analyzed using descriptive statistics in the form of mean, median, standard deviation, minimum score, maximum score, frequency distribution, and percentage. The results showed that the physical fitness level of the SDN 3 Batulicin football team was in the moderate category. These findings confirm that the students already possess a sufficient basic level of physical ability to participate in football activities, although it is not yet fully optimal to support stable and sustainable performance. Thus, the main premise of this study is confirmed: physical fitness is an important aspect that deserves attention in the development of youth football. This study recommends the need for a more structured, gradual, and age-appropriate physical training program, tailored to the characteristics of elementary school students, in order to improve physical fitness quality and support the achievement of better performance outcomes.     Keyword: Physical Fitness; Indonesian Physical Fitness Test; Soccer; Elementary School Students.